Is My Body Extended in Time? On Stefan Swieżawski’s Intriguing Suggestion That Corporeal Substance Is a Spatiotemporal Solid - Piwowarczyk, Marek (Roczniki Filozoficzne, 2025)
In this paper I would like to consider a suggestion that can be found in Stefan Swieżawski’s article The Central Problem of the Thomistic Doctrine of the Soul (Commensuratio animae ad hoc corpus). In it, he holds that corporeal substance is a space-time solid, which can be read as a claim that corporeal substance extends in time, i.e. it has temporal parts. Typically, the view that things have temporal parts is considered to oppose substantialism, because it is a form of processualism. I would like to show that the possession of temporal parts can be reconciled with being a substance, as long as we bear in mind the irreducibility of the substantial subject to temporal parts and as long as we want to maintain the view that the substantial subject is wholly present at each moment of its persistence. I first show three ways of understanding the body in Aristotelian philosophy (body as quantity, as substance and as matter), then I focus on the body conceived of as quantity (extension). I emphasize the accidental character of the body understood this way and present its connections with the substantial subject (distinguished from accidents). Then I present Swieżawski’s suggestion and give two interpretations of it: (1) that substance is temporally determined (exists in time) but has no temporal parts and (2) that substance has temporal parts. I further explore the latter interpretation, first indicating the sources that could have inspired Swieżawski. Next, I develop Swieżawski’s idea in the context of the analytical dispute about identity in time.